2007
DOI: 10.3177/jnsv.53.383
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Sesame Seed and Its Lignan Increase Both Ascorbic Acid Concentration in Some Tissues and Urinary Excretion by Stimulating Biosynthesis in Rats

Abstract: SummaryWe previously showed that the intake of sesamin, a major lignan in sesame seed, decreased lipid peroxidation and elevated tocopherol concentration in rat tissues. In this study, we examined the effect of dietary sesame seed and sesamin on the ascorbic acid concentration in rat tissues. Rats (4-wk-old) were fed either a vitamin E-free diet, or a diet containing 50 mg ␥ -tocopherol/kg, one containing 2 g sesamin/kg, one containing 50 mg ␥ -tocopherol/kg and 2 g sesamin/kg, or one containing 200 g sesame s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 41 publications
(37 reference statements)
1
3
0
Order By: Relevance
“…The accumulation of vitamin E acts by detoxifying the hydroxyl and proxy radicals, leading to reduced lipid peroxidation, or by reducing excess tissue aldehydes [ 11 ]. This is supported by many previous studies, in which supplementation of either vitamin E or sesamin and sesamolin demonstrated that these antioxidants inhibit lipid peroxidation [ 3 - 7 , 25 ]. The antioxidant effect is likely to contribute to the decreased endothelial dysfunction from free radicals [ 26 ], resulting in an increase in the vasorelaxing factor, nitric oxide (NO) [ 27 ].…”
Section: Discussionsupporting
confidence: 75%
“…The accumulation of vitamin E acts by detoxifying the hydroxyl and proxy radicals, leading to reduced lipid peroxidation, or by reducing excess tissue aldehydes [ 11 ]. This is supported by many previous studies, in which supplementation of either vitamin E or sesamin and sesamolin demonstrated that these antioxidants inhibit lipid peroxidation [ 3 - 7 , 25 ]. The antioxidant effect is likely to contribute to the decreased endothelial dysfunction from free radicals [ 26 ], resulting in an increase in the vasorelaxing factor, nitric oxide (NO) [ 27 ].…”
Section: Discussionsupporting
confidence: 75%
“…Among the 11 kinds of the metabolites, mono-and dicatechol metabolites, which appear to be metabolized by P450s, are known to have high antioxidative activities (Nakai et al, 2003;Miyake et al, 2005). It was reported that sesamin elevated CYP2B and CYP4A mRNA levels in rats (Tsuruoka et al, 2005;Ikeda et al, 2007) and CYP1A activity in rainbow trout (Trattner et al, 2008). In addition, sesamin inhibited CYP4F2 to elevate tocopherol levels (Sontag and Parker, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that sesame ingestion benefits postmenopausal women by improving blood lipids, antioxidant status, and possibly sex hormone status. Ikeda and others (2007) studied the effect of dietary sesame seed and sesamin on the ascorbic acid concentration in rat tissues. The dietary sesame seeds and sesamin elevated ascorbic acid concentrations in the liver and kidney and increased urinary excretion in those Wistar rats.…”
Section: Introductionmentioning
confidence: 99%